MOORE–PENROSE INVERSE OF BIDIAGONAL MATRICES. I - Hakopian, Yu.R.; Aleksanyan, S.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
In the present paper we deduce closed form expressions for the entries of the Moore–Penrose inverse of a special type upper bidiagonal matrices. On the base of the formulae obtained, a finite algorithm with optimal order of computational complexity is constructed.